Pengaruh Manajemen Risiko, Intellectual Capital, Profitabilitas dan Ukuran Perusahaan Terhadap Nilai Perusahaan: pada perusahaan sub sektor farmasi yang terdaftar di IDX Industrial Classification tahun 2018 - 2022 - Aprilia, Lidiya; Wardoyo, Dwi Urip (Owner : Riset dan Jurnal Akuntansi, 2024)
Firm value is an investor's view of the company as seen through the stock price, the higher the stock price, it will indicate that the company has a high corporate value. That’s urgents of pharmaceuticals company to maintain company value. On the other hand, company value attracts potential investors to invest and increase public confidence in using the company's products. Finding effect of risk management, intellectual capital, profitability and company size on firm value in pharmaceutical sub-sector companies listed on the IDX Industry Classification for 2018 – 2022. This research uses quantitative methods. Data obtained from financial reports. The population used is the pharmaceutical sub-sector companies listed on the IDX Industry Classification of 12 companies. The data was processed using a purposive sampling technique. There is  9 companies for the period 2018 – 2022, so that 45 observations were obtained. The analytical method used is panel data regression analysis. Results of this study indicate that intellectual capital has a positive effect and company size has a negative effect on firm value. While risk management and profitability have no effect on firm value